2010
DOI: 10.1080/19485561003709263
|View full text |Cite
|
Sign up to set email alerts
|

Significant Effects of Fatwa-Based Perception on Contraceptive Practice Among Muslim Women in South Jordan Under the Early Stage of Fertility Transition

Abstract: An interview survey of 450 Muslim women in a rural village of south Jordan under the early stage of fertility transition was conducted to explore major causes of contraceptive use, taking both their sociodemographic attributes and fatwa (Islamic jurisprudence)-based perception into account. Discriminant analysis, which was performed for the subject women divided into 15- to 29-, 30- to 39-, and 40- to 49-year age groups, revealed that "the number of living children" in the former and "to do contraception for g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…This might be explained by the greater number of educational materials and centres available for women in urban areas, which may make the effect of the women's education minimal or disappear. Previous Jordanian studies have found that education level and economic status play an essential role in influencing the use of contraceptive methods (20)(21)(22)(23), but these studies did not examine the effect of the woman's education level on selecting the type of contraceptive method. Other studies have also found the association still holding between education and use of family planning methods.…”
Section: Discussionmentioning
confidence: 99%
“…This might be explained by the greater number of educational materials and centres available for women in urban areas, which may make the effect of the women's education minimal or disappear. Previous Jordanian studies have found that education level and economic status play an essential role in influencing the use of contraceptive methods (20)(21)(22)(23), but these studies did not examine the effect of the woman's education level on selecting the type of contraceptive method. Other studies have also found the association still holding between education and use of family planning methods.…”
Section: Discussionmentioning
confidence: 99%
“…From the personal domain, knowledge about family planning methods and available health services was discussed as a factor influencing women's SRH [19-21, 25, 26, 28, 30, 32, 33, 35, 39, 43-45, 47-53, 68, 70, 77, 79, 80, 83, 86, 87, 89, 90]. Insufficient knowledge about contraception and lack of basic reproductive knowledge was reported as one of the main barriers to contraception use among Muslim women [20,26,29,31,39,41,46,83,90,91]. Some women are unaware of services available for them [69,74,75,78,87], particularly unmarried women [74,75,78].…”
Section: Theme 1: Insufficient Knowledge and Misconceptions About Conmentioning
confidence: 99%
“…While the other group strongly oppose the use of family planning, except when used for medical reasons [76,82,86,88,89,91]. For many women, the use of family planning is believed to be permissible in Islam as long as it is used for child spacing and not limiting the number of children [46,86,88,89,91].…”
Section: Theme 7: Religious and Cultural Barriers To Family Planningmentioning
confidence: 99%
“…Religious leaders are important opinion leaders in Jordan and can influence women's contraceptive use [11,12]. A previous study found RLs to be equally or more knowledgeable than the general public about matters of reproductive health and family planning, so they could be a positive influence [7].…”
Section: Introductionmentioning
confidence: 99%